Bioapplications of graphene constructed functional nanomaterials. (25th January 2017) - Gulzar, Arif; Yang, Piaoping; He, Fei; Xu, Jiating; Yang, Dan; Xu, Liangge; Jan, Mohammad Omar
Abstract: Graphene has distinctive mechanical, electronic, and optical properties, which researchers have applied to develop innovative electronic materials including transparent conductors and ultrafast transistors. Lately, the understanding of various chemical properties of graphene has expedited its application in high-performance devices that generate and store energy. Graphene is now increasing its terrain outside electronic and chemical applications toward biomedical areas such as precise bio sensing through graphene-quenched fluorescence, graphene-enhanced cell differentiation and growth, and graphene-assisted laser desorption/ionization for mass spectrometry. In this Account, we evaluate recent efforts to apply graphene and graphene oxides (GO) to biomedical research and a few different approaches to prepare graphene materials designed for biomedical applications and a brief perspective on their future applications. Because of its outstanding aqueous processability, amphiphilicity, surface functionalizability, surface enhanced Raman scattering (SERS), and fluorescence quenching ability, GO chemically exfoliated from oxidized graphite is considered a promising material for biological applications. In addition, the hydrophobicity and flexibility of large-area graphene synthesized by chemical vapor deposition (CVD) allow this material to play an important role in cell growth and differentiation. Graphene is considered to be an encouraging and smart candidate for numerous biomedical applications such as NIR-responsive cancer therapy and fluorescence bio-imaging and drug delivery. To that end, suitable preparation and unique approaches to utilize graphene-based materials such as graphene oxides (GOs), reduced graphene oxides (rGOs), and graphene quantum dots (GQDs) in biology and medical science are gaining growing interest. Highlights: General properties of Graphene and recent progress in the graphene and its bioapplications. Graphene derivatives and their optical properties were discussed. Magnetic Resonance imaging (MRI) and multifunctional graphene based MRI agents where discussed. Graphene based therapeutic agents and drug delivery carriers where discussed. Cytotoxicity, antibacterial properties and graphene scaffold culture where deliberated upon.